PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PADA TIM FUTSAL SMA NEGERI 5 SIJUNJUNG (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of interval training on endurance in the Futsal team at SMA Negeri 5 Sijunjung. This study used a one group pretest-postest design approach. In the design there is a pretest, before being given treatment. Thus the results of treatment can be known to be more accurate, because it can be compared with the conditions before being treated and after being given treatment. After that, the Posttest Balke was carried out, the data obtained were analyzed descriptively, then the research hypothesis was tested according to the problem, namely: "There is an effect of Interval Training (X) training on increasing endurance (Y). Based on the analysis carried out, the t value between the initial test and the final test of Interval Training training on endurance with t table at a significant level of 0.05 with degrees of freedom N - 1 (14-1 = 13). This shows that the value of tcount (13.6)> ttable (1.771), thus it can be concluded that the hypothesis that there is an effect of Interval Training (X) training on endurance (Y) on the Futsal team at SMA Negeri 5 Sijunjung. Key Words: Interval Training, Endurance